A Novel Method for Reduction of a Double Bond by using a Microwave Oven - Dave, M.A.; Prabhu, P.J. (Asian Journal of Chemistry, 2010)
The reduction of tetralone benzylidine derivatives (I-A and I-B) was carried out to give the corresponding benzyl derivatives (II-A and II-B) in a microwave oven. Higher yields are obtained in much lesser time than that obtained in conventional method.